Catastrophe insurance - Ang, Tin Tin (2013)
This report is a study on catastrophe insurance. It gives an insight in to five particular aspects of catastrophe, namely, the catastrophe risk management, reinsurance, underwriting procedures and factors, claims process, structure of a catastrophe insurance programme and future of catastrophe insurance. The Great Hanshin-Awaji Earthquake and the Hurricane Andrew are discussed in detail, as examples of earthquake andhurricence. We trust that the report will complement the knowledge that is acquired from the school studies. The report dwells more on the practical aspects, as observed by us from literature review and interviews with practising professionals. We hope that this report provides the relevant information on the subject and that readers will find it interesting.